Analysis of performance measures to improve the quality of service in cloud based e-government web portal. (2018) - Priya, Vedhanayagam; Subha, S.; Balamurugan, Balusamy
Online registration system (ORS) is an Indian government digital initiative under the policy of e-Kranti. This sector needs high quality of service (QoS) as it is crowded with numerous patients for various requisitions. In this paper, a stochastic queueing model is proposed to study a single virtual machine queue with batch arrivals and two types of different services (registration and appointment) one after the other in series. After getting this service, a certain batch of patient's may need an additional service from the ORS portal or they may quit. We also considered patient's impatient behaviour wherein batch of patients decide not to take any service in the ORS portal. We attain steady-state results and probability generating functions and the properties of several parameters on the virtual machine performance are analysed numerically. These results can help the management to calculate the service level of the web portal and to improve the performance.